Gulmore, the Boss - Harris, Frank, 1856-1931 (Salt Lake City, UT : Project Gutenberg, 2007)
"Gulmore, the Boss" by Frank Harris is a novel written in the late 19th century. The story centers around Jonathan Byrne Gulmore, a powerful political figure, and explores the dynamics of his household, particularly the interactions with his daughter Ida and her complicated emotions towards Professor Roberts, a young and influential academic. The novel delves into themes of ambition, social class, and the corrupt nature of political systems, as Gulmore prepares for an upcoming election that could reshape his power in the community. The opening of the novel introduces us to the Gulmore household, where the parents and their daughter engage in a tense conversation about the impending election and a competing candidate, Professor Roberts. Mr. Gulmore expresses his disdain for Roberts, seeking information about him to use against him. Meanwhile, Ida struggles with her feelings for the professor, initially dismissing him but revealing her jealousy as she becomes aware of his influence. We see her conflicted emotions manifest through her desire for her father's approval and her underlying ambition to rise within the social hierarchy. The stage is set for a conflict between the traditional political power represented by Gulmore and the emerging ideals of a reform-minded academic, foreshadowing the tensions that will unfold as the election approaches. (This is an automatically generated summary.)
Release date is 2007-10-12
Produced by David Widger
Keywords: Fiction